Silver particle dispersion
Patent Information
- Application Number
- JP2023100997
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-21
- Filing Date
- 2023-06-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-02-21
AI Technical Summary
Existing methods face challenges in achieving high dispersibility and storage stability of metal fine particles while allowing for low-temperature sintering, particularly when using resin substrates like polyimide or polyethylene terephthalate, as the dispersibility and stability hinder effective low-temperature sintering.
The use of an acrylic resin with a polyalkylene glycol moiety and functional groups such as carboxylic acid groups at the ends of the main chain, which enhances dispersibility and storage stability, allowing for easy removal and low-temperature sintering of metal fine particles.
The acrylic resin ensures high dispersibility and storage stability of metal fine particles, enabling efficient low-temperature sintering and forming conductive films, suitable for applications like fine electrodes and circuits.
Abstract
Description
[Technical Field]
[0001] The present invention relates to an acrylic resin used as a dispersant for, for example, a metal fine particle dispersion, a method for producing the same, and the metal fine particle dispersion. [Background technology]
[0002] To form fine electrodes, circuits, and the like for electronic components, it has been proposed to use a metal particle dispersion in which metal particles (metal nanoparticles) with particle sizes of several to several tens of nanometers are dispersed in a dispersion medium. Metal particle dispersions are also called metal inks or metal pastes. Metal pastes are conductive pastes containing binder resins. After the metal particle dispersion is applied to a substrate, energy such as heat or light is applied, causing the metal particles to sinter or the binder resin to harden, forming a conductive film.
[0003] Highly active metal particles tend to sinter even at low temperatures and are unstable as particles. Therefore, various methods have been investigated to prevent sintering and aggregation of metal particles and improve storage stability.
[0004] For example, a method using an acrylic resin having a specific structure as a binder resin has been investigated. Patent Document 1 proposes a method using a (meth)acrylic resin with a glass transition temperature of 50°C or less, obtained by polymerizing a monomer mixture containing a polyoxyethylene (meth)acrylate monomer. Patent Document 2 also proposes a binder resin for conductive paste, which has a main chain composed of segments derived from a (meth)acrylate monomer and is composed of a polymer having a phosphoric acid component at the ω-position. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2010-135180 [Patent Document 2] International Publication No. 2011 / 001908 Brochure Summary of the Invention [Problem to be solved by the invention]
[0006] As the substrate to which the metal particle dispersion is applied, glass, ceramics, and also resins (polyimide, polyethylene terephthalate, polyethylene naphthalate, etc.) are used. When using such resins as the substrate, it is necessary to set the baking temperature to a low temperature of about 100 to 200°C.
[0007] However, the higher the dispersibility and storage stability of the metal fine particles, the more difficult it is to sinter the metal fine particles at low temperatures. [Means for solving the problem]
[0008] One aspect of the present invention relates to an acrylic resin that contains units of a (meth)acrylate monomer A having a polyalkylene glycol moiety and has, at at least one terminal, a functional group selected from the group consisting of a carboxylic acid group and a carboxylate salt group.
[0009] Another aspect of the present invention relates to a metal fine particle dispersion containing the above acrylic resin, metal fine particles, and a dispersion medium.
[0010] Yet another aspect of the present invention relates to a method for producing an acrylic resin, comprising: a step of preparing a polymerization liquid containing a (meth)acrylate monomer A having a polyalkylene glycol moiety, a polymerization initiator, and a chain transfer agent, wherein at least one of the chain transfer agent and the polymerization initiator has at least one functional group selected from the group consisting of a carboxylic acid group and a carboxylate salt group; and a step of polymerizing the (meth)acrylate monomer A in the polymerization liquid to synthesize an acrylic resin containing units of the (meth)acrylate monomer A and having the functional group at at least one terminal. [Effects of the Invention]
[0011] By using the acrylic resin according to the present invention, it is possible to obtain a metal fine particle dispersion in which the dispersibility and storage stability of metal fine particles are improved and the firing of metal fine particles can proceed even at low temperatures.
[0012] The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. DETAILED DESCRIPTION OF THE INVENTION
[0013] The acrylic resin according to an embodiment of the present invention contains a (meth)acrylate monomer unit A having a polyalkylene glycol moiety, and has a functional group selected from the group consisting of a carboxylic acid group and a carboxylate salt group at at least one terminal.
[0014] In this specification, the term "acrylic resin" is used to include methacrylic resin, and acrylate and methacrylate may be collectively referred to as "(meth)acrylate."
[0015] By having not only a polyalkylene glycol moiety but also a carboxylic acid group and / or a carboxylic acid salt group at at least one end of the main chain, the acrylic resin exhibits excellent performance as a dispersant for metal particle dispersions used in forming electrodes, circuits, etc. The carboxylic acid group and / or the carboxylic acid salt group at the end of the main chain is thought to have a moderate interaction with the metal particles.
[0016] An acrylic resin containing units of (meth)acrylate monomer A as well as units of (meth)acrylate monomer B having a hydrophobic group can function as a dispersant with an excellent balance of hydrophilicity and hydrophobicity. The hydrophilic polyalkylene glycol moiety is thought to interact with the surface of the metal microparticles. Meanwhile, the hydrophobic moiety is thought to be located outside the polyalkylene glycol moiety when viewed from the metal microparticles, thereby maintaining the distance between the metal microparticles. As a result, the dispersibility and storage stability of the metal microparticles are thought to be improved.
[0017] The presence of a carboxylic acid group and / or a carboxylate salt group at at least one end of the acrylic resin main chain is thought to reduce steric hindrance compared to when the carboxylic acid group and / or a carboxylate salt group are not present at the end of the main chain. This is thought to facilitate a stronger interaction between the carboxylic acid group and / or a carboxylate salt group and the metal fine particles. Therefore, the balance of hydrophilicity and hydrophobicity of the acrylic resin and the synergistic effect of the carboxylic acid group and / or a carboxylate salt group present at the end of the main chain are thought to result in high dispersibility and storage stability of the metal fine particles. Furthermore, the metal fine particles are thought to have a relatively strong interaction only with the end of the acrylic resin main chain, which is thought to facilitate the acrylic resin's detachment from the metal fine particles and facilitate the firing process even at low temperatures.
[0018] The acrylic resin and its manufacturing method, as well as the metal fine particle dispersion using the acrylic resin according to the embodiments of the present invention will be described in more detail below.
[0019] [Acrylic resin] The acrylic resin contains units derived from a (meth)acrylate monomer A (hereinafter sometimes referred to as monomer A) having a polyalkylene glycol moiety. Monomer A is a raw material monomer for the acrylic resin. Examples of monomer A include mono(meth)acrylates having a polyalkylene glycol moiety. Examples of polyalkylene glycols corresponding to the polyalkylene glycol moiety include polyethylene glycol, polypropylene glycol, and copolymers of ethylene glycol and propylene glycol. One type of monomer A may be used alone, or two or more types may be used in combination. Furthermore, one type of monomer A may have two or more types of polyalkylene glycol moieties.
[0020] The mono(meth)acrylate having a polyalkylene glycol moiety is not particularly limited, and examples thereof include a monomer in which a hydroxyl group at one end of a polyalkylene glycol is substituted with a (meth)acryloyloxy group, and a monomer in which a hydroxyl group at one end of a polyalkylene glycol is substituted with a (meth)acryloyloxy group and a hydroxyl group at the other end is substituted with -OR (R is a hydrocarbon group which may have a substituent, etc.). R is an alkyl group (C 1-26 Alkyl group or C 1-20 alkyl groups), alicyclic hydrocarbon groups (cycloalkyl groups), and aryl groups (C 6-14 Examples of the substituents that R may have include a hydroxyl group, an alkoxy group, and / or an ester group.
[0021] The mono(meth)acrylate having a polyalkylene glycol moiety is not particularly limited, but examples thereof include methoxypolyethylene glycol mono(meth)acrylate, octoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate, stearoxypolyethylene glycol mono(meth)acrylate, stearoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, allyloxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, and hydroxyl group-terminated polyethylene glycol mono(meth)acrylate. Note that "polyethylene glycol-polypropylene glycol" refers to a block copolymer moiety of ethylene glycol and propylene glycol.
[0022] In addition, (meth)acrylates commercially available under the trade names Light Ester 130MA and Light Ester 041MA (both manufactured by Kyoeisha Chemical Co., Ltd.); NK Ester M-90G and NK Ester M-230G (both manufactured by Shin-Nakamura Chemical Co., Ltd.); Blenmer PME, Blenmer AME, Blenmer 50POEP-800B, Blenmer 50AOEP-800B, Blenmer ALE, Blenmer PSE, Blenmer ASEP, Blenmer PKEP, Blenmer AKEP, Blenmer PME, Blenmer AME, and Blenmer PE-350 (all manufactured by NOF Corporation) can also be used.
[0023] Considering the use of an acrylic resin as a dispersant for a metal particle dispersion, the acrylic resin preferably contains at least a unit of a (meth)acrylate monomer containing a polyethylene glycol unit. Furthermore, in the units of monomer A contained in the acrylic resin, the polyalkylene glycol moiety preferably contains at least a polyethylene glycol moiety. Polymerization of monomer A having a polyethylene glycol moiety tends to proceed stably, and the desired hydrophilic moiety can be easily imparted to the resulting acrylic resin as a dispersant for metal particles. Therefore, when the resulting acrylic resin is used as a dispersant for a metal particle dispersion, the dispersibility and storage stability of the metal particles are improved.
[0024] The repeat number of alkylene glycol units (or oxyalkylene units) in the polyalkylene glycol moiety is preferably 4 to 120, and more preferably 9 to 90. Monomer A having such a polyalkylene glycol moiety tends to undergo stable polymerization and can easily impart the desired hydrophilic moiety as a dispersant for metal fine particles to the resulting acrylic resin. This improves the dispersibility and storage stability of metal fine particles. When one type of monomer A has two or more types of polyalkylene glycol moieties (for example, when monomer A contains block copolymerization moieties of different alkylene glycols), the total repeat number of alkylene glycol units is preferably within the above range.
[0025] In addition to units derived from monomer A, the acrylic resin preferably contains units derived from a (meth)acrylate monomer B (hereinafter also referred to as monomer B) having a hydrophobic group. Monomer B is a raw material monomer for the acrylic resin. The units derived from monomer B can easily provide the acrylic resin with hydrophobic moieties that are desirable as a dispersant for metal fine particles. Examples of hydrophobic groups include hydrocarbon groups (aliphatic, alicyclic, or aromatic hydrocarbon groups). Examples of aliphatic hydrocarbon groups include alkyl groups. Examples of alkyl groups include C 1-26 Alkyl groups include C 1-20The alkyl group may be methyl, ethyl, propyl, butyl, hexyl, decyl, stearyl, etc. Specific examples of the alkyl group include methyl, ethyl, propyl, butyl, hexyl, decyl, and stearyl groups. The alicyclic hydrocarbon group may be a cycloalkyl group (C 4-10 Cycloalkyl group or C 5-8 Cycloalkyl groups (e.g., cyclopentyl, cyclohexyl, etc.), bridged cyclic hydrocarbon groups (C 6-20 Examples of the aromatic hydrocarbon group include an aryl group (C 6-20 Aryl group or C 6-14 Specific examples of the aryl group include a phenyl group, a tolyl group, and a naphthyl group. The aliphatic hydrocarbon group (such as an alkyl group) may have an alicyclic hydrocarbon group and / or an aromatic hydrocarbon group as a substituent. The alicyclic hydrocarbon group and the aromatic hydrocarbon group may each have an aliphatic hydrocarbon group as a substituent. These hydrocarbon groups as substituents are selected from the hydrocarbon groups exemplified above, and include, for example, C 1-4 Alkyl group, C 5-8 Cycloalkyl groups, C 6-10 Examples include an aryl group.
[0026] Preferred examples of monomer B include alkyl (meth)acrylates, (meth)acrylates having an aliphatic hydrocarbon group, and aryl (meth)acrylates. These monomers may have a substituent. Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-stearyl (meth)acrylate, and benzyl (meth)acrylate. Examples of (meth)acrylates having an aliphatic hydrocarbon group include cycloalkyl (meth)acrylates (e.g., cyclohexyl (meth)acrylate), and (meth)acrylates having a crosslinked cyclic hydrocarbon group (e.g., isobornyl (meth)acrylate). Examples of aryl (meth)acrylates include phenyl (meth)acrylate and tolyl (meth)acrylate. However, the monomer B is not limited to these. The monomer B may be used alone or in combination of two or more.
[0027] Among these monomers B, it is preferable to use alkyl (meth)acrylates in which the hydrophobic group is an alkyl group. When the hydrophobic group is an alkyl group, the resulting acrylic resin exhibits hydrophobicity, which is more desirable as a dispersant for metal fine particles. This improves the dispersibility and storage stability of the metal fine particles. In addition, the resulting acrylic resin is more easily detached from the metal fine particles, facilitating low-temperature firing.
[0028] The acrylic resin may have units derived from a monomer C that are different from the units derived from monomer A and the units derived from monomer B. As the monomer C, a monomer that has little effect on the hydrophilicity and hydrophobicity obtained from monomer A and monomer B, and on the performance (e.g., thermal decomposition) of the acrylic resin as a dispersant is selected. The monomer C is not particularly limited to an acrylic monomer as long as it is polymerizable with monomer A and / or monomer B. However, from the viewpoint of ease of polymerization with monomer A and / or monomer B, an acrylic monomer (such as (meth)acrylate) is preferred. As the monomer C, for example, glycidyl methacrylate, glycerin monomethacrylate, N,N,N-trimethyl-N-(2-hydroxy-3-methacryloyloxypropyl)-ammonium chloride, urethane acrylate, etc. may be selected.
[0029] A monomer having a heterocycle may be used as the monomer C. When the acrylic resin contains a unit derived from a monomer having a heterocycle, high adhesion to the substrate can be ensured. Examples of heteroatoms contained in the heterocycle include an oxygen atom, a nitrogen atom, and a sulfur atom. The heterocycle may have one or more heteroatoms. The number of heteroatoms contained in the heterocycle is not particularly limited and may be one or two or more. The number of heteroatoms contained in the heterocycle may be, for example, four or less or three or less. These lower and upper limits can be arbitrarily combined. The heterocycle may be either saturated or unsaturated. The heterocycle may be, for example, a three- or more-membered ring, or a four- or more-membered ring, or a five- or more-membered ring. The heterocycle may be, for example, a three- to eight-membered ring (or six- or less), a four- to eight-membered ring (or six- or less), or a five- to eight-membered ring (or six- or less).
[0030] Examples of the monomer C having a heterocycle include (meth)acrylates having a heterocycle. Examples of the monomer C having a heterocycle include (meth)acrylates of hydroxy compounds having a heterocycle (such as alkyl alcohols having a heterocycle). Examples of the heterocycle include oxygen-containing rings (such as tetrahydrofuran, dioxolane, furan, tetrahydropyran, and dioxane), nitrogen-containing rings (such as pyrrolidine, pyrrole, imidazoline, and pyrimidine), sulfur-containing rings (such as tetrahydrothiophene and thiophene), and heterocycles having two or more heteroatoms (such as oxazole, thiazole, and morpholine). Examples of the alkyl alcohol include C 1-10 Alkyl alcohol (C 1-6 Alkyl alcohol or C 1-4 Examples of alkyl alcohols include methanol, ethanol, propanol, 2-propanol, butanol, and hexanol. Among these, (meth)acrylates having an oxygen-containing ring (for example, furfuryl (meth)acrylate) are preferred because they are easily available and can easily ensure high adhesion to the substrate.
[0031] In an acrylic resin containing units of monomer A, monomer B, and optionally other monomer C, the content of monomer A units is preferably 10% to 50% by mass, more preferably 15% to 30% by mass. In this case, the acrylic resin exhibits hydrophilicity suitable for use as a dispersant for a metal microparticle dispersion. Furthermore, when synthesizing the acrylic resin, the hydrophilicity is not too high, and polymerization of the monomers proceeds stably. The content of monomer A units corresponds to the mass ratio of monomer A to the total amount of raw material monomers for the acrylic resin.
[0032] The content of the monomer B unit is preferably 50% by mass to 90% by mass, and more preferably 70% by mass to 85% by mass. In this case, the acrylic resin exhibits hydrophobicity suitable for use as a dispersant for a metal fine particle dispersion. The content of the monomer B unit corresponds to the mass ratio of the monomer B to the total amount of raw material monomers of the acrylic resin.
[0033] The content of the monomer C unit is, for example, 30% by mass or less, preferably 10% by mass or less. From the viewpoint of easily ensuring high adhesion, the content of the monomer C unit is preferably 1% by mass or more. The content of the monomer C unit corresponds to the mass proportion of the monomer C in the total amount of raw material monomers of the acrylic resin.
[0034] The acrylic resin has a functional group selected from the group consisting of a carboxylic acid group and a carboxylic acid salt group at at least one end of the main chain. While the number of carboxylic acid groups and / or carboxylic acid salt groups is not particularly limited, it is preferable that the acrylic resin has a carboxylic acid group and / or a carboxylic acid salt group at one end of the main chain. In this case, the hydrophobic portion of the acrylic resin is more likely to expand spatially in the metal particle dispersion, making it easier to maintain an appropriate distance between the metal particles. While the acrylic resin may have the above-mentioned functional groups on its side chains, from the viewpoint of easily maintaining an appropriate distance between the metal particles, it is preferable that the number of functional groups is small, and it is even more preferable that the acrylic resin does not have the above-mentioned functional groups on its side chains.
[0035] Examples of the carboxylate salt include ammonium salts and metal salts. Examples of the metal salt include alkali metal salts (sodium salts, potassium salts, etc.) and alkaline earth metal salts (calcium salts, etc.).
[0036] The introduction of a carboxylic acid group and / or a carboxylate salt group into at least one end of the main chain of the acrylic resin can be confirmed, for example, by measuring the acid value or amine value of the acrylic resin by the following method. When a carboxylic acid group and / or a carboxylate salt group is introduced into at least one end of the main chain of the acrylic resin, the acid value or amine value is, for example, 3 mg / g to 15 mg / g.
[0037] (acid number) Dissolve 1 g of the sample acrylic resin in 100 g of isopropanol. The resulting solution is subjected to neutralization titration with 0.1 N potassium hydroxide solution using phenolphthalein as an indicator, and the acid value of the acrylic resin can be determined by measuring the amount (mg) of potassium hydroxide required to neutralize 1 g of acrylic resin.
[0038] (amine value) Dissolve 1 g of the sample acrylic resin in 100 g of isopropanol. The resulting solution is subjected to neutralization titration with 0.1 N hydrochloric acid using methyl orange as an indicator, and the amount (mg) of potassium hydroxide equivalent to the acid required to neutralize 1 g of acrylic resin can be measured to determine the amine value of the acrylic resin.
[0039] The weight-average molecular weight of the acrylic resin is preferably 5,000 to 100,000, and more preferably 10,000 to 50,000. This is because the viscosity of the metal particle dispersion containing the acrylic resin does not become too high, and the dispersibility and storage stability of the metal particles are improved. In addition, since the acrylic resin is easily decomposed at low temperatures, the metal particles can be easily fired at low temperatures. The weight-average molecular weight can be measured, for example, by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0040] [Acrylic resin manufacturing method] The method for producing an acrylic resin according to this embodiment includes, for example, a step of preparing a polymerization liquid containing a (meth)acrylate monomer A having a polyalkylene glycol moiety, a polymerization initiator, and a chain transfer agent, wherein at least one of the chain transfer agent and the polymerization initiator has at least one carboxylic acid group and / or carboxylic acid salt group; and a step of polymerizing the monomer A in the polymerization liquid to synthesize an acrylic resin containing units of the monomer A and having a carboxylic acid group and / or a carboxylic acid salt group at at least one terminal.
[0041] The polymerization liquid contains a monomer A, and if necessary, a monomer B, and may also contain another monomer C.
[0042] The content of monomer A and the content of monomer B in the total monomers may be selected depending on the desired structure of the acrylic resin.
[0043] The total content of the monomers in the polymerization liquid (monomer concentration) is preferably 30% by mass to 80% by mass, and more preferably 40% by mass to 70% by mass, because this allows the polymerization reaction of the monomers to proceed easily.
[0044] The method for introducing a carboxylic acid group and / or a carboxylate salt group into at least one end of the main chain is not particularly limited, but examples include a method in which a polymerization initiator having at least one carboxylic acid group and / or a carboxylate salt group, a chain transfer agent having at least one carboxylic acid group and / or a carboxylate salt group, or the like is used when synthesizing an acrylic resin. Either one of these polymerization initiators or chain transfer agents may be used, or both polymerization initiators and chain transfer agents may be used in combination. Furthermore, a carboxylic acid group and / or a carboxylate salt group may be introduced into only one end of the main chain of the acrylic resin, or a carboxylic acid group and / or a carboxylate salt group may be introduced into both ends of the main chain.
[0045] Acrylic resins are synthesized by polymerizing monomer A, monomer B, and, if necessary, other monomers C, using known polymerization methods such as radical polymerization or cationic polymerization. Polymerization is initiated by a polymerization initiator that decomposes when exposed to heat or light to generate radicals or ions. Therefore, in the synthesis of acrylic resins, polymerization initiators that decompose when exposed to heat or light to generate radicals or ions are used.
[0046] The polymerization initiator having at least one carboxylic acid group and / or carboxylic acid salt group is not particularly limited, but examples thereof include disuccinic acid peroxide, 4,4'-azobis(4-cyanovaleric acid), and salts thereof (ammonium salt, sodium salt, potassium salt, calcium salt, etc.). Commercially available initiators such as Perloyl SA (manufactured by Nippon Oil & Fats Co., Ltd.) and V-501 (manufactured by Wako Pure Chemical Industries, Ltd.) can also be used. These polymerization initiators may be used alone or in combination of two or more. Among them, disuccinic acid peroxide is preferred due to its high initiator efficiency.
[0047] The chain transfer agent having at least one carboxylic acid group and / or carboxylic acid salt group is not particularly limited, but examples thereof include mercaptocarboxylic acids (2-mercaptopropionic acid, 3-mercaptopropionic acid, mercaptoacetic acid, mercaptosuccinic acid, etc.) and their salts (ammonium salts, sodium salts, potassium salts, calcium salts, etc.). These chain transfer agents may be used alone or in combination of two or more. Among them, 3-mercaptopropionic acid is preferred because it allows for easy adjustment of the weight-average molecular weight of the acrylic resin.
[0048] The polymerization initiator and chain transfer agent contained in the polymerization liquid may be a polymerization initiator or chain transfer agent having a carboxylic acid group and / or a carboxylate group, or a polymerization initiator and chain transfer agent not having a carboxylic acid group and / or a carboxylate group. As such a polymerization initiator and chain transfer agent, for example, known ones can be used.
[0049] The polymerization initiator not having a carboxylic acid group and / or a carboxylic acid salt group is not particularly limited, and a polymerization initiator used for polymerizing a normal (meth)acrylate monomer can be used. Examples include azo-based polymerization initiators (such as azobisisobutyronitrile (AIBN)) and organic peroxide-based polymerization initiators (such as peroxyketals, hydroperoxides, dialkyl peroxides, peroxydicarbonates, diacyl peroxides, and peroxyesters). These may be used alone or in combination of two or more.
[0050] The content of the polymerization initiator in the polymerization liquid is preferably 0.1 to 5 parts by mass, and more preferably 0.2 to 3 parts by mass, per 100 parts by mass of the total amount of monomers, which increases the polymerization rate and makes it difficult for excess unreacted initiator to remain after polymerization.
[0051] The chain transfer agent without a carboxylic acid group and / or a carboxylic acid salt group is not particularly limited, and examples thereof include thiol compounds. Examples of such chain transfer agents include alkyl mercaptans (e.g., n-butyl mercaptan, t-butyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, etc.), and mercaptocarboxylic acid esters (e.g., alkyl mercaptopropionates (2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, stearyl-3-mercaptopropionate, etc.)). These may be used alone or in combination of two or more.
[0052] The content of the chain transfer agent in the polymerization liquid is preferably 0.1 to 10 parts by mass, and more preferably 0.2 to 5 parts by mass, per 100 parts by mass of the total amount of monomers, which makes it easier to synthesize an acrylic resin having a desired weight-average molecular weight.
[0053] In addition to the monomer, polymerization initiator, and chain transfer agent, the polymerization liquid may contain, for example, a solvent, as necessary. The type of solvent is appropriately selected from known solvents depending on the monomer, etc. For example, esters (ethyl acetate, butyl acetate, etc.), hydrocarbons (toluene, etc.), ethers (methyl cellosolve, dioxane, butyl carbitol, etc.), ketones (methyl ethyl ketone, methyl isobutyl ketone, etc.), terpenes (terpene alcohols (dihydroterpineol, terpineol, etc.), esters of terpene alcohols (dihydroterpineol acetate, etc.)), etc.) may be used. One type of solvent may be used alone, or two or more types may be used in combination.
[0054] When preparing the polymerization liquid, the monomer, polymerization initiator, chain transfer agent, solvent, etc. may be mixed simultaneously or added in order, or some of the components may be mixed and then the remaining components may be added. For example, a polymerization liquid containing the monomer, polymerization initiator, chain transfer agent, and solvent may be mixed at room temperature, heated, and then the polymerization initiator may be added.
[0055] Polymerization is initiated by a polymerization initiator. At least monomer A is polymerized in a polymerization solution, and the main chain polymerization reaction is terminated with a chain transfer agent to synthesize an acrylic resin containing units of monomer A. At this time, since at least one of the chain transfer agent and the polymerization initiator contains a carboxylic acid group and / or a carboxylic acid salt group, a carboxylic acid group and / or a carboxylic acid salt group is introduced into at least one end of the main chain of the acrylic resin.
[0056] The method for preparing the polymerization liquid and the method for polymerizing the polymerization liquid are not particularly limited. For example, a polymerization liquid is prepared by placing predetermined amounts of monomers, a chain transfer agent, a solvent, etc. in a separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen gas inlet, and stirring the mixture.
[0057] The polymerization solution is bubbled with nitrogen gas to remove dissolved oxygen from the polymerization solution, and then the atmosphere in the separable flask is replaced with nitrogen gas and the temperature is raised to a predetermined temperature while stirring. Next, a solution of a polymerization initiator diluted with a solvent is added to the polymerization solution to initiate polymerization. After a predetermined time from the start of polymerization, the reaction solution is cooled to room temperature to terminate the polymerization, and the solvent is dried and removed to obtain an acrylic resin.
[0058] The polymerization temperature is determined appropriately depending on the type of monomer, etc., and is, for example, 60 to 100° C. The polymerization time is determined appropriately depending on the type of monomer, polymerization temperature, etc., and is, for example, 2 to 24 hours.
[0059] [Metal fine particle dispersion] The acrylic resin according to this embodiment can be suitably used as a dispersant for a metal fine particle dispersion. The metal fine particle dispersion contains metal fine particles, a dispersant, and a dispersion medium.
[0060] The metal particle dispersion of this embodiment uses an acrylic resin as a dispersant that not only has a polyalkylene glycol moiety but also has a carboxylic acid group and / or a carboxylic acid salt group at at least one end of the main chain, thereby providing high dispersibility and storage stability for the metal particles. Furthermore, when the metal particle dispersion is baked, the dispersant is easily removed from the metal particles, and baking proceeds easily even at low temperatures. Therefore, the metal particle dispersion of this embodiment can be suitably used as a metal ink or metal paste used to form fine electrodes, circuits, etc. of electronic components.
[0061] Generally, metal ions and metal pastes differ in the amount of dispersion medium they contain. Dispersions with a high amount of dispersion medium and low viscosity are called metal inks. Dispersions with a low amount of dispersion medium and high viscosity are called metal pastes. Therefore, metal microparticle dispersions may be either metal inks or metal pastes, depending on the application.
[0062] Metallic materials for forming metal microparticles include simple metals and alloys. Metallic elements contained in simple metals or alloys include typical metal elements and transition metal elements. Typical metal elements include zinc (Zn), aluminum (Al), gallium (Ga), indium (In), germanium (Ge), tin (Sn), lead (Pb), antimony (Sb), and bismuth (Bi). Transition metal elements include titanium (Ti), zirconium (Zr), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), ruthenium (Ru), cobalt (Co), nickel (Ni), palladium (Pd), platinum (Pt), silver (Ag), copper (Cu), and gold (Au). The alloy preferably contains two or more of these metal elements. In particular, it is preferable to contain at least one selected from silver and copper, and the metal material is preferably Ag alone, an Ag alloy, Cu alone, a Cu alloy, etc. Furthermore, the metal fine particles may contain two or more types of metal fine particles made of different materials.
[0063] The average particle size of the metal particles is preferably 5 nm to 500 nm, and more preferably 5 nm to 100 nm. By using metal particles having such an average particle size, sintering at low temperatures can be easily carried out, and the conductivity of the formed conductive film can also be increased.
[0064] The average particle size is the particle size at 50% cumulative volume (D50) in the volume particle size distribution. The average particle size (D50) can be measured by a laser diffraction scattering method using a laser diffraction particle size distribution measuring device.
[0065] The shape of the metal fine particles is not particularly limited, and may be any of a sphere, an oval sphere, a polygonal column, a polygonal pyramid, a flat shape (thin plate, scale, flake, etc.), or a similar shape, etc. From the viewpoint of easily increasing contact between the metal fine particles, a sphere, an oval sphere, a flat shape, or a similar shape is preferred.
[0066] The metal particles may be commercially available, formed by evaporating a metal material, or produced by chemical reaction in a liquid or gas phase.
[0067] The metal fine particle dispersion preferably contains 10% to 80% by mass, and more preferably 20% to 70% by mass of metal fine particles, in order to improve dispersibility.
[0068] The content of the acrylic resin (dispersant) contained in the metal fine particle dispersion is preferably 0.5 to 10 parts by mass, and more preferably 1 to 5 parts by mass, per 100 parts by mass of the metal fine particles (or colloid of metal fine particles described below). When the content of the acrylic resin is within this range, the dispersibility and storage stability of the metal fine particles are improved, and decomposition of the acrylic resin during firing is also likely to occur.
[0069] The dispersion medium for the metal fine particle dispersion may be a liquid dispersion medium, such as alcohol, ether, ester, ketone, or hydrocarbon. Terpenes are also included in the dispersion medium. One type of dispersion medium may be used alone, or two or more types may be used in combination.
[0070] Examples of alcohols include methanol, ethanol, and cyclohexanol. Examples of ethers include aliphatic ethers (chain ethers, such as diethyl ether, butyl carbitol, and methyl cellosolve), and cyclic ethers (tetrahydrofuran, and the like). Examples of esters include aliphatic esters (ethyl acetate, butyl acetate, and ethyl butyrate, and the like). Examples of ketones include aliphatic ketones (chain ketones, such as acetone, ethyl methyl ketone, and methyl isobutyl ketone), and alicyclic ketones (cyclohexanone, and the like). Examples of hydrocarbons include aliphatic hydrocarbons (hexane, and the like), alicyclic hydrocarbons (cyclohexane, and the like), and aromatic hydrocarbons (benzene and toluene, and the like). Examples of terpenes include terpene alcohols (dihydroterpineol, terpineol, and the like), and esters of terpene alcohols (dihydroterpineol acetate, and the like).
[0071] The metal fine particle dispersion may contain a stabilizer in addition to the metal fine particles, dispersant, and dispersion medium. By using the stabilizer, the metal fine particles in the metal fine particle dispersion can be prevented from agglomerating and can be kept at an appropriate distance from each other, thereby stabilizing the metal fine particles.
[0072] The stabilizer may be added when preparing the metal fine particle dispersion, but is preferably used in a state where it is coordinated with the metal fine particles (metal colloid). The stabilizer may be coordinated with the metal fine particles by mixing it with the metal fine particles and heating it as necessary, or by using the stabilizer during the preparation of the metal fine particles.
[0073] As the stabilizer, for example, an organic compound having a polar functional group that coordinates with the metal fine particles and a hydrophobic organic group is used. Examples of the polar functional group include an amino group, a mercapto group, an oxygen-containing group (a hydroxy group (including a phenolic hydroxy group), a carbonyl group, an ester group, a carboxy group, etc.). The stabilizer may contain one type of polar functional group or two or more types.
[0074] Among these, it is preferable to use organic amines, which are compounds containing amino groups, in terms of room temperature stability. The organic amines may be any of primary amines, secondary amines, and tertiary amines, and may be any of cyclic amines and chain amines. In terms of ease of coordination with metal fine particles, primary amines (especially primary chain amines) are preferred. As organic amines, for example, alkylamines (hexylamine, octylamine, decylamine, dodecylamine, myristylamine, etc.) are preferred. In terms of high dispersion stability of metal fine particles and ease of removal during the firing process, C 6-14 Alkylamine or C 8-12 Alkylamines are preferred.
[0075] Although amines with a small number of carbon atoms are highly reactive and may result in reduced storage stability, when the acrylic resin of the present invention is used as a dispersant, high storage stability can be ensured even when such amines with a small number of carbon atoms are used.
[0076] The stabilizer is preferably removed at an appropriate stage in the firing process, and is therefore preferably a low molecular weight compound (for example, a compound having a molecular weight of 500 or less).
[0077] The amount of stabilizer contained in the metal fine particle dispersion (preferably stabilizer coordinated to the metal fine particles) is, for example, 0.1 to 5 parts by mass, and preferably 0.2 to 2 parts by mass, per 100 parts by mass of the metal fine particles. When the amount of stabilizer is within this range, the metal fine particles are easily stabilized in the metal fine particle dispersion and are also easily removed during firing.
[0078] The metal fine particle dispersion may contain known additives (for example, a leveling agent, an adhesion promoter, etc.) as needed.
[0079] The metal particle dispersion according to the present invention has high dispersibility of metal particles and high storage stability. For example, the prepared metal particle dispersion shows no precipitation even after storage at 25°C for one month.
[0080] In the metal fine particle dispersion according to the present invention, the firing of the metal fine particles proceeds sufficiently even at a low temperature of about 100 to 200° C. Therefore, a resin substrate (for example, a substrate formed of a resin such as polyimide, polyethylene terephthalate, or polyethylene naphthalate) can be used as the substrate to which the metal fine particle dispersion is applied.
[0081] That sintering proceeds sufficiently even at low temperatures can be confirmed, for example, by sintering a metal particle dispersion using the method described below and measuring the volume resistivity. If the volume resistivity shows a low value of 20 μΩ·cm or less, sintering is evaluated as having proceeded sufficiently.
[0082] (Firing) A dispersion of metal particles is applied to a glass substrate using a bar coater, and then heated and baked at 120°C for 30 minutes using a blower dryer.
[0083] (volume resistivity) The surface resistivity is measured using a low resistivity meter with the four-probe method, and the volume resistivity is calculated by converting it into the film thickness measured with a contact film thickness meter. [Example]
[0084] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0085] [Example 1] (1) Synthesis of acrylic resin (dispersant) A 1 L separable flask equipped with a stirrer, a condenser, a thermometer, a hot water bath, and a nitrogen gas inlet was mixed with 100 parts by mass of a monomer mixture containing 22% by mass of methoxypolyethylene glycol monomethacrylate (monomer A, trade name "Light Ester 041MA", manufactured by Kyoeisha Chemical Co., Ltd., number of oxyethylene repeat units = 30) and 78% by mass of isobutyl methacrylate (IBMA, monomer B), 1 part by mass of 3-mercaptopropionic acid (chain transfer agent), and 100 parts by mass of butyl carbitol (solvent) to obtain a polymerization liquid.
[0086] The polymerization solution was bubbled with nitrogen gas for 20 minutes to remove dissolved oxygen, and then the atmosphere in the separable flask was replaced with nitrogen gas and the temperature was raised to 80°C while stirring. Next, a solution prepared by diluting 0.5 parts by mass of azobisisobutyronitrile (AIBN, polymerization initiator) with butyl carbitol was added to the polymerization solution. 15 hours after the start of polymerization, the reaction solution was cooled to room temperature to terminate the polymerization, yielding a butyl carbitol solution of acrylic resin. 2,000 parts by mass of water was added to the resulting solution, which was then stirred, filtered, and dried to remove the butyl carbitol.
[0087] The obtained acrylic resin was evaluated according to the following procedure. The obtained acrylic resin was analyzed by gel permeation chromatography (GPC) using a column (product name "GPC KF-802", manufactured by Showa Denko K.K.). The weight average molecular weight in terms of polystyrene was 15,000. In addition, the acrylic resin was found to be a compound represented by the formula (1):
[0088] [ka]
[0089] The structure shown in the figure was confirmed by nuclear magnetic resonance ( 1 This was confirmed by measurement using H-NMR (400 MHz, manufactured by JEOL Ltd.) and by measurement of the acid value using the method described above. Formula (1) shows that methoxypolyethylene glycol monomethacrylate and isobutyl methacrylate are randomly copolymerized. In formula (1), n is 30. The acid value was 8 mg / g.
[0090] (2) Preparation of metal particle dispersion (metal ink) (2-1) Preparation of silver colloid 20 g of silver nitrate, 100 g of isobutanol, and 100 g of dodecylamine (a stabilizer) were mixed. The mixture was heated to 100°C and then refluxed for 5 hours. The solids in the resulting mixture were recovered by settling using centrifugation. The recovered solids were washed three times with methanol and then centrifuged to recover a silver colloid in which dodecylamine was coordinated with silver particles.
[0091] (2-2) Preparation of silver particle dispersion 100 parts by mass of the silver colloid prepared in (2-1), 1 part by mass of the acrylic resin prepared in (1), and 100 parts by mass of cyclohexanol (dispersion medium) were mixed. After stirring with a homogenizer, the mixture was filtered and purified through a 1 μm filter to prepare a silver microparticle dispersion. In the silver microparticle dispersion, the silver microparticles were 50% by mass, and the dodecylamine was 0.2 parts by mass per 100 parts by mass of silver microparticles.
[0092] The average particle diameter of the silver particles was 40 nm. The particle diameter at 50% cumulative volume (D50) of the volume particle size distribution, which can be measured by laser diffraction scattering using a laser diffraction particle size distribution analyzer (product name "Nanotrac WaveII-EX150", manufactured by Microtrack Bell Co., Ltd.), was defined as the average particle diameter.
[0093] (3) Evaluation of silver particle dispersion (3a) Evaluation of dispersion stability The obtained silver particle dispersion was stored for one month at 25° C., and then the presence or absence of precipitation was checked. The absence of precipitation was evaluated as A, and the presence of precipitation was evaluated as B.
[0094] (3b) Evaluation of low-temperature firing A dispersion of silver particles was applied to a glass substrate using a bar coater and then baked for 30 minutes at 120°C using a fan dryer. The surface resistivity was measured using the four-probe method with a low resistivity meter (product name "Loresta AX MCP-T370", manufactured by Mitsubishi Chemical Analytech Co., Ltd.), and the volume resistivity was calculated by converting the surface resistivity into the film thickness measured with a contact film thickness meter (product name "Dektak XT-E", manufactured by Bruker Corporation).
[0095] (3c) Evaluation of substrate adhesion The adhesion of the silver particle dispersion coating to the substrate was evaluated using the cross-cut method in accordance with JIS K5600-5-6:1999. Specifically, the silver particle dispersion was applied to a glass substrate using a bar coater and dried at 120°C for 30 minutes to form a 2 μm-thick coating. The coating was then cut into 2 mm x 2 mm squares (cross-cut) using a cutter. A 25 mm-wide piece of transparent pressure-sensitive adhesive tape, cut to a length of approximately 75 mm, was attached to the center of the cut so that the tape touched the center of the cut. The tape was pressed and rubbed against the cut with a finger so that at least a 20 mm long section near the center of the tape was flat. The tape was then quickly peeled off at a 90° angle within 5 minutes of application. The percentage (%) of the cut area where the tape was attached that remained unpeeled was determined, and the substrate adhesion was evaluated based on this percentage. A higher percentage indicates better substrate adhesion.
[0096] [Example 2] A silver particle dispersion was prepared and evaluated in the same manner as in Example 1, except that the blending amount of the acrylic resin was changed to 3 parts by mass.
[0097] [Example 3] A silver fine particle dispersion was prepared and evaluated in the same manner as in Example 1, except that the blending amount of the acrylic resin was changed to 5 parts by mass.
[0098] [Example 4] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that the amount of chain transfer agent used in synthesizing the acrylic resin was 0.2 parts by mass. The synthesized acrylic resin had the structure shown in formula (1), n was 30, the acid value was 3 mg / g, and the weight-average molecular weight was 45,000.
[0099] [Example 5] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that the amount of chain transfer agent used in synthesizing the acrylic resin was 5 parts by mass. The synthesized acrylic resin had the structure shown in formula (1), n was 30, the acid value was 15 mg / g, and the weight-average molecular weight was 9,000.
[0100] [Example 6] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that when synthesizing the acrylic resin, "Light Ester 130MA" (methoxypolyethylene glycol monomethacrylate, manufactured by Kyoeisha Chemical Co., Ltd., number of oxyethylene repeat units = 9) was used as monomer A instead of "Light Ester 041MA." The synthesized acrylic resin had the structure shown in formula (1), n was 9, the acid value was 9 mg / g, and the weight average molecular weight was 16,000.
[0101] [Example 7] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that, when synthesizing the acrylic resin, "NK Ester M-230G" (methoxypolyethylene glycol monomethacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., number of oxyethylene repeat units = 23) was used as monomer A instead of "Light Ester 041MA." The synthesized acrylic resin had the structure shown in formula (1), with n being 23, an acid value of 7 mg / g, and a weight-average molecular weight of 17,000.
[0102] [Example 8] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that when synthesizing the acrylic resin, "Blenmer PME4000" (methoxypolyethylene glycol monomethacrylate, manufactured by NOF Corporation, number of oxyethylene repeat units = 90) was used as monomer A instead of "Light Ester 041MA."
[0103] The synthesized acrylic resin had the structure shown in formula (1), with n being 90, an acid value of 7 mg / g, and a weight-average molecular weight of 19,000.
[0104] [Example 9] When synthesizing the acrylic resin, disuccinic acid peroxide (trade name "Perloil SA", manufactured by Nippon Oil & Fats Co., Ltd.) was used as the initiator instead of AIBN. Dodecanethiol was used as the chain transfer agent instead of 3-mercaptopropionic acid. Except for these, an acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2.
[0105] The synthesized acrylic resin has the formula (2):
[0106] [ka]
[0107] The polymer had the structure shown in the following formula (2). Formula (2) shows that methoxypolyethylene glycol monomethacrylate and isobutyl methacrylate were randomly copolymerized. In formula (2), n is 30. The acid value was 8 mg / g and the weight-average molecular weight was 20,000.
[0108] [Example 10] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 9, except that when synthesizing the acrylic resin, "Light Ester 130MA" (methoxypolyethylene glycol monomethacrylate, manufactured by Kyoeisha Chemical Co., Ltd., number of oxyethylene repeat units = 9) was used as monomer A instead of "Light Ester 041MA." The synthesized acrylic resin had the structure shown in formula (2), n was 9, the acid value was 9 mg / g, and the weight-average molecular weight was 21,000.
[0109] [Example 11] An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 9, except that, when synthesizing the acrylic resin, "NK Ester M-230G" (methoxypolyethylene glycol monomethacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., number of oxyethylene repeat units = 23) was used as monomer A instead of "Light Ester 041MA." The synthesized acrylic resin had the structure shown in formula (2), with n being 23, an acid value of 10 mg / g, and a weight-average molecular weight of 19,000.
[0110] [Example 12] When synthesizing the acrylic resin, "Blenmer PME4000" (methoxypolyethylene glycol monomethacrylate, manufactured by NOF Corporation, number of oxyethylene repeat units = 90) was used as monomer A instead of "Light Ester 041-MA." Except for this, an acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 9. The synthesized acrylic resin had the structure shown in formula (2), with n being 90, an acid value of 7 mg / g, and a weight-average molecular weight of 17,000.
[0111] [Comparative Example 1] 10 parts by mass of silver colloid and 90 parts by mass of cyclohexanol were mixed and stirred with a homogenizer, and then filtered and purified with a 1 μm filter to prepare a silver particle dispersion. No acrylic resin was blended into the silver particle dispersion. The prepared silver particle dispersion was evaluated in the same manner as in Example 1.
[0112] Comparative Example 2 An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that, when synthesizing the acrylic resin, dodecanethiol was used as the chain transfer agent instead of 3-mercaptopropionic acid in an amount of 2 parts by mass per 100 parts by mass of the monomer mixture.
[0113] Comparative Example 3 An acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 2, except that Monomer A was not used when synthesizing the acrylic resin.
[0114] Comparative Example 4 When synthesizing the acrylic resin, the amount of monomer A was 21 parts by mass, the amount of monomer B was 77 parts by mass, and 2 parts by mass of methacrylic acid (MA) was further used as a monomer. Except for these, an acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Comparative Example 2. The synthesized acrylic resin has the formula (3):
[0115] [ka]
[0116] The polymer had the structure shown in the following formula (3). Formula (3) shows that methoxypolyethylene glycol monomethacrylate, isobutyl methacrylate, and methacrylic acid were randomly copolymerized. In formula (3), n is 30. The acid value was 10 mg / g, and the weight-average molecular weight was 16,000.
[0117] [Example 13] When synthesizing the acrylic resin, the amount of monomer B was set to 73 parts by mass, and further, "Light Ester THF (1000)" (tetrahydrofurfuryl methacrylate, manufactured by Kyoeisha Chemical Co., Ltd.) was used as another monomer C. Except for these, an acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 5. The acid value of the synthesized acrylic resin was 15 mg / g and the weight average molecular weight was 34,000.
[0118] [Example 14] When synthesizing the acrylic resin, the amount of monomer B was set to 73 parts by mass, and "SR611" (alkoxylated tetrahydrofurfuryl acrylate, manufactured by Sartomer Corporation) was used as another monomer C. Except for these, an acrylic resin and a silver particle dispersion were prepared and evaluated in the same manner as in Example 5. The acid value of the synthesized acrylic resin was 15 mg / g and the weight average molecular weight was 23,000.
[0119] The compositions of the dispersants in the examples and comparative examples are shown in Table 1. The results of the examples and comparative examples are shown in Table 2. Table 1 also shows the raw materials and amounts (charged amounts) of the dispersants, as well as the blending ratio of the dispersants to the silver colloid.
[0120] [Table 1]
[0121] [Table 2]
[0122] As shown in the table, the metal particle dispersions of Examples 1 to 14, which used an acrylic resin having a polyalkylene glycol moiety and a carboxylic acid group at the end of the main chain as a dispersant, showed high dispersibility and storage stability, with no precipitation observed even after storage for one month at 25°C. In addition, the volume resistivity after firing was low, indicating that firing at low temperatures had progressed sufficiently.
[0123] On the other hand, in Comparative Examples 2 to 4, like the metal fine particle dispersion of Comparative Example 1 in which no dispersant was used, precipitation was observed after storage at 25°C for one month, and the dispersion stability and storage stability were low. In addition, the surface resistivity after firing was high and could not be measured. This indicated that firing at low temperatures was also insufficient.
[0124] From the above, it has been revealed that a metal particle dispersion using an acrylic resin having a polyalkylene glycol moiety and a carboxylic acid group at the end of the main chain has high dispersibility and storage stability. Furthermore, it has been found that even when such a metal particle dispersion is baked at a low temperature, the baking of the metal particles proceeds sufficiently even at a low temperature.
[0125] Furthermore, in Examples 13 and 14, which contained a monomer unit having a heterocycle, high adhesion to the substrate was ensured.
[0126] While the present invention has been described in terms of presently preferred embodiments, such disclosure is not to be interpreted as limiting. Various changes and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. It is therefore intended that the appended claims be interpreted to cover all changes and modifications that do not depart from the true spirit and scope of the invention. [Industrial Applicability]
[0127] By using the acrylic resin according to the present invention, it is possible to obtain a metal particle dispersion that has high dispersibility and storage stability of metal particles and in which the calcination of the metal particles contained in the metal particle dispersion proceeds sufficiently even at low temperatures. The obtained metal particle dispersion is useful for metal inks and metal pastes used to form fine electrodes and circuits of electronic components. However, the applications are not limited to these, and the acrylic resin can be used for a variety of applications.
Claims
1. An acrylic resin comprising units of a (meth)acrylate monomer A having a polyalkylene glycol moiety, and having at least one terminal functional group selected from the group consisting of a carboxylic acid group and a carboxylic acid salt group.
2. 2. The acrylic resin according to claim 1, wherein the number of repeating alkylene glycol units in the polyalkylene glycol moiety is 4 to 120.
3. The acrylic resin according to claim 1 or 2, wherein the polyalkylene glycol moiety comprises a polyethylene glycol moiety.
4. The acrylic resin according to any one of claims 1 to 3, further comprising a unit of a (meth)acrylate monomer B having a hydrophobic group.
5. The acrylic resin according to claim 4 , wherein the hydrophobic group is an alkyl group.
6. 6. The acrylic resin according to claim 4, wherein the content of the (meth)acrylate monomer A unit in the acrylic resin is 10 to 50 mass%.
7. The acrylic resin according to any one of claims 1 to 6, having a weight average molecular weight of 5,000 to 100,000.
8. The acrylic resin according to any one of claims 1 to 7, further comprising a unit of a monomer C having a heterocycle.
9. The acrylic resin according to claim 8 , wherein the monomer C comprises at least a unit of a (meth)acrylate monomer having an oxygen-containing ring.
10. A metal fine particle dispersion comprising the acrylic resin according to any one of claims 1 to 9, metal fine particles, and a dispersion medium.
11. The metal fine particle dispersion according to claim 10 , wherein the metal comprises at least one selected from silver and copper.
12. a step of preparing a polymerization liquid containing a (meth)acrylate monomer A having a polyalkylene glycol moiety, a polymerization initiator, and a chain transfer agent, wherein at least one of the chain transfer agent and the polymerization initiator has at least one functional group selected from the group consisting of a carboxylic acid group and a carboxylate salt group; and a step of polymerizing the (meth)acrylate monomer A in the polymerization liquid to synthesize an acrylic resin containing units of the (meth)acrylate monomer A and having the functional group at at least one end.
13. The method for producing an acrylic resin according to claim 12, wherein the chain transfer agent comprises 3-mercaptopropionic acid.
14. The method for producing an acrylic resin according to claim 12 or 13, wherein the polymerization initiator comprises disuccinic acid peroxide.